Can medium-sized cities become Creative Cities? Discussing the cases of three Central and Western European cities - Chapain, Caroline; Lange, Bastian; Stachowiak, Krzysztof (Rozwój Regionalny i Polityka Regionalna, 2013)
This paper aims to explore the concept of Creative City from the points of view of three medium-sized cities in Central and Western Europe: Birmingham (UK), Leipzig (Germany) and Poznań (Poland). The concept of Creative City has risen in popularity in the last 15 years but its meanings and its policy application display important variations. In an attempt to clarify conceptual issues and policy approaches around the term of Creative City, Scott (2006) states that policy makers should focus on specific key variables when attempting to build viable Creative Cities: the presence of inter-firm networks of producers combined with a flexible local labour market. Infrastructural facilities and social capital are also crucial in this process. Even though these variables may be mostly found in largescale metropolitan areas such as New York, Los Angeles etc., Scott (2006, p. 9) argues that “there are also many small and specialised creative agglomerations all over the world” due to the process of increased differentiation. In addition, Hall (2004) argues that building a truly Creative City is possible but is a long-term process, and historical favourable preconditions are important.